Empowering colistin effectiveness: Origanum majorana essential oil enhances antibacterial and antibiofilm potency against mcr-1-positive Gram-negative bacteria, preventing drug resistance development - Zine El Abidine Bzazou El Ouazzani; Laila Reklaoui; Houda Benaicha; Said Barrijal (Novel Research in Microbiology Journal)
Escherichia coli and Klebsiella pneumonia; along with other Gram-negative bacteria (GNB), are known for their resilience to a broad spectrum of antibiotics, including last-resort options such as colistin, which is regarded as the last line of defense in treating multidrugresistant (MDR) infections. This elevated level of resistance presents a substantial threat to the healthcare system, paving the way for a post-antibiotic era. In the present study, a checkerboard assay was employed to pinpoint the optimal combinations of Origanum majorana (OM) essential oil and colistin (CS) for the purpose of enhancing colistin's antibacterial and antibiofilm activities (FICI ≤ 0.5). The investigation focused on eight colistin-resistant (CS_R) bacterial isolates, with a particular focus on two strains carrying the mobile colistin resistance mcr-1 gene. The CS@OM combination resulted in a 2- to 16-fold improvement of colistin efficacy, resulting in a biofilm eradication rate ranging from ∼ 52 % to 82 %. Furthermore, it evinced a complete eradication of the free-floating cells of the isolates, inclusive of those harboring the mcr-1 gene. The bactericidal activity of the CS@OM combination was achieved through various mechanisms, including bacterial membrane disruption and leakage of internal bacterial constituents, leading to bacterial death. Consequently, the CS@OM combination evinced a high capacity to prevent the development of drug resistance in the examined isolates. To the best of our knowledge, this is the first study to appraise the combination of colistin and Origanum majorana essential oil against colistinresistant isolates, including those carrying mcr-1 gene with the aim of regaining colistin susceptibility.